Response to Cabergoline treatment in Invasive Prolactinoma with hemorrhage- A case report - Pant, Vivek; Baral, Suman; Aryal, Binod; Tumbapo, Arjun (Journal of Diabetes and Endocrinology Association of Nepal, 2018)
Patients with invasive prolactinoma present with constellation of symptoms including headache, blurred vision, lethargy, menstrual irregularity and sexual dysfunction. Cabergoline, a potent dopamine agonist, is a known medication prescribed for the treatment of prolactinoma. Here, we report a case of invasive macroprolactinoma with hemorrhage in a 18 years female with dramatic response to cabergoline treatment clinically, biochemically, and radiologically.Jour of Diab and Endo Assoc of Nepal 2017; 1(1): 18-20